2022
DOI: 10.1038/s41598-022-19593-8
|View full text |Cite
|
Sign up to set email alerts
|

Simple diagnosis of cancer by detecting CEA and CYFRA 21-1 in saliva using electronic sensors

Abstract: One way of early diagnosis of cancer is by detecting the biomarkers that get introduced into easily accessible body fluids. We report the development of portable and rapid electronic biosensors for quantitative detection of two secretive cancer biomarkers–Carcinoembryonic antigen (CEA) and Cytokeratin fragment 19 (CYFRA 21-1). The reduced graphene oxide (rGO)/ melamine (MEL)/antibodies/ bovine serum albumin (BSA) based devices were tested for 1 pg/mL to 800 ng/mL of CEA and CYFRA 21-1. The responses of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Joshi et al reported a portable and rapid electronic biosensor device based on reduced graphene oxide (rGO), melamine (MEL), antibodies, and bovine serum albumin (BSA) to quantitatively detect CYFRA21-1 in saliva. The device was tested from 1 pg/mL to 800 ng/mL of CYFRA21-1 and the corresponding response of the sensors ranged from 6.18% to 64% [ 117 ]. Jian et al used an electrochemiluminescence (ECL) immunosensor based on an electrochemically induced atom transfer radical polymerization (eATRP) process to detect CYFRA21-1.…”
Section: Biomarkers and Their Biosensorsmentioning
confidence: 99%
“…Joshi et al reported a portable and rapid electronic biosensor device based on reduced graphene oxide (rGO), melamine (MEL), antibodies, and bovine serum albumin (BSA) to quantitatively detect CYFRA21-1 in saliva. The device was tested from 1 pg/mL to 800 ng/mL of CYFRA21-1 and the corresponding response of the sensors ranged from 6.18% to 64% [ 117 ]. Jian et al used an electrochemiluminescence (ECL) immunosensor based on an electrochemically induced atom transfer radical polymerization (eATRP) process to detect CYFRA21-1.…”
Section: Biomarkers and Their Biosensorsmentioning
confidence: 99%
“…Saliva collection can be easily performed in a clinical setting or even at home, making it convenient for patients [ 9 ]. Saliva diagnostics also offer the advantage of the early detection of diseases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, cancer has been a prominent cause of mortality globally, with approximately 9.7 million fatalities recorded in 2022 as per the International Agency for Research on Cancer (IARC) report 1 that can increase to approximately 16 million by 2040. 2 Among the various types of cancers, oral cancer ranks as the sixth most prevalent cancer worldwide. 3,4 It commonly occurs in areas including the gingiva, the oor of the mouth, the buccal mucosa, and the lateral edge of the tongue.…”
Section: Introductionmentioning
confidence: 99%